The Association of Nanostructured Carbonated Hydroxyapatite with Denatured Albumin and Platelet-Rich Fibrin: Impacts on Growth Factors Release and Osteoblast Behavior - Renata de Lima Barbosa; Neilane Rodrigues Santiago Rocha; Emanuelle Stellet Lourenço; Victor Hugo de Souza Lima; Elena Mavropoulos; Rafael Coutinho Mello-Machado; Carolina Spiegel; Carlos Fernando Mourão; Gutemberg Gomes Alves (Journal of Functional Biomaterials, 2024)
Platelet-rich Fibrin (PRF), a second-generation blood concentrate, offers a versatile structure for bone regeneration due to its composition of fibrin, growth factors, and cytokines, with adaptations like denatured albumin-enriched with liquid PRF (Alb-PRF), showing potential for enhanced stability and growth factor dynamics. Researchers have also explored the combination of PRF with other biomaterials, aiming to create a three-dimensional framework for enhanced cell recruitment, proliferation, and differentiation in bone repair studies. This study aimed to evaluate a combination of Alb-PRF with nanostructured carbonated hydroxyapatite microspheres (Alb-ncHA-PRF), and how this association affects the release capacity of growth factors and immunomodulatory molecules, and its impact on the behavior of MG63 human osteoblast-like cells. Alb-PRF membranes were prepared and associated with nanocarboapatite (ncHA) microspheres during polymerization. MG63 cells were exposed to eluates of both membranes to assess cell viability, proliferation, mineralization, and alkaline phosphatase (ALP) activity. The ultrastructural analysis has shown that the spheres were shattered, and fragments were incorporated into both the fibrin mesh and the albumin gel of Alb-PRF. Alb-ncHA-PRF presented a reduced release of growth factors and cytokines when compared to Alb-PRF (p < 0.05). Alb-ncHA-PRF was able to stimulate osteoblast proliferation and ALP activity at lower levels than those observed by Alb-PRF and was unable to positively affect in vitro mineralization by MG63 cells. These findings indicate that the addition of ncHA spheres reduces the biological activity of Alb-PRF, impairing its initial effects on osteoblast behavior.